Is lactate threshold an appropriate marker for competitive cyclists? - Kenefick, R. W.; Mahood, N. V.; Mattern, C. O.; Quinn, T. J. (Medicine & Science in Sports & Exercise, 2000)
This investigation compared physiological variables during a 20-km time trial with those corresponding to athletes' lactate thresholds. Male cyclists (N = 13) performed a graded protocol to determine lactate threshold. Following eight minutes of rest, VO2max was determined by having Ss cycle at lactate-threshold wattage for one minute, with workload being increased by 20 W every minute until volitional exhaustion. On a separate occasion, a self-paced 20-km time trial was completed. All variables measured during the time trial were greater than those at lactate threshold. For over 30 minutes, power output (26+%), heart rate (15+%), VO2 (25+%), and lactate level (79+%) greatly exceeded lactate threshold values. Implication. While lactate threshold might be correlated with performance, it is not a representative intensity for extended cycling races. It is not an appropriate training intensity.